Learn to Tango with D - Bell, Kris Macleod (Apress, 2012)
¡ DON CLUGSTON is a physicist who has worked in the solar photovoltaics industry since 1994. An expatriate Australian, he is currently living with his wife and three children in Leipzig, Germany. He has published papers on highly insulated windows, environmental philosophy, Biblical theology, C++ programming, and semiconductor device physics. After 14 years of experience with C++, Don made his first contributions to D and its standard library in 2005. Since that time, he has had a major influence on the development of the D language, especially with regard to mathematics and generic programming. He is responsible for Tango's mathematics library.p